2018
DOI: 10.4236/tel.2018.83031
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Mandatory Corporate Social Responsibility—A Literature Review Perspective

Abstract: The purpose of this paper is to discuss the implications of mandatory corporate social responsibility (CSR) contributions: the CSR levy. Using public interest theory as the theoretical lens, this paper adopts a pro-regulation approach and justifies the introduction of the CSR levy in Mauritius, based on the economic and business environment prevailing at the time. Secondary literature sources are used to investigate. Two further questions related to mandatory CSR are investigated: Does the CSR levy result in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Corporate philanthropic giving during COVID-19 may also have been opportunistically motivated by the self-interested desire to enhance goodwill among consumers, employees, and communities, and thus such giving was also indirectly economically motivated (Chen et al, 2022 ). While in some countries, corporate philanthropy can also be legally mandated for large companies (e.g., India, Mauritius, Indonesia, Nepal, see: Ramdhony, 2018 ), and thus would also fall under the legal CSR domain, for most corporations, philanthropy is completely volitional. In any event, while the COVID-19 crisis is clearly a threat to the economic sustainability of many businesses along with the overall material well-being of society, it has at the same time presented many opportunities for companies to stand apart from their competitors by engaging in philanthropic activities (Fernández-Feijóo Souto, 2009 ; Maas & Liket, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Corporate philanthropic giving during COVID-19 may also have been opportunistically motivated by the self-interested desire to enhance goodwill among consumers, employees, and communities, and thus such giving was also indirectly economically motivated (Chen et al, 2022 ). While in some countries, corporate philanthropy can also be legally mandated for large companies (e.g., India, Mauritius, Indonesia, Nepal, see: Ramdhony, 2018 ), and thus would also fall under the legal CSR domain, for most corporations, philanthropy is completely volitional. In any event, while the COVID-19 crisis is clearly a threat to the economic sustainability of many businesses along with the overall material well-being of society, it has at the same time presented many opportunities for companies to stand apart from their competitors by engaging in philanthropic activities (Fernández-Feijóo Souto, 2009 ; Maas & Liket, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Past literature shows that firms are also exposed to risk in light of external stakeholders' backslash for greenwashing (Szabo & Webster, 2020). Further, research has shown that retaining human capital can be an important outcome (Ramdhony, 2018). Ambiguity and aspirational talk about CSR may benefit employee engagement, talent retention, and attraction, impacting firm capabilities and operational efficiency (Winkler et al, 2020).…”
Section: Greenwashingmentioning
confidence: 99%
“…Países desenvolvidos têm sido mais cautelosos em negociar com países emergentes, a fim de evitar negociar com empresas corruptas ou ligadas ao trabalho escravo e discriminação. Países como África do Sul, China, Dinamarca, França e Malásia têm adotado o sistema mandatório de divulgação de RSC (Ramdhony, 2018).…”
Section: Hipóteseunclassified